Pengenalan Teknologi Augmented Reality sebagai Media Pembelajaran Anak Usia Dini di RA Babul Ulum Desa Pulau Panggung Kecamatan Abung Tinggi Kabupaten Lampung Utara - Poppy Puspitasari; Avita Ayu Permanasari; Sukarni Sukarni (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
In this millennial era, there are many school institutions that use modern technology in carrying out learning, to support and make learning more interesting. One example of modern technology that can be used is Augmented Reality technology. Unfortunately the use of Augmented Reality technology is not as easy as imagined, because there are obstacles such as the lack of teacher education about various learning media that support the learning process and also especially on the location factor of RA Babul Ulum which is in rural areas so that it has not been touched by learning media that smells technology. To support learning using the AR system at RA Babul Ulum, Pulau Panggung village, North Lampung, a community grant team from the State University of Malang funded by PNBP carried out a community service program in the form of counseling and providing teaching aids in the form of an LCD projector and also several Augmented Reality (AR) cards.). With the methods of observation, lectures, demonstrations, discussions and practice with direct trials resulted in: teachers RA Babul Ulum understand and master the application of Augmented Reality technology; RA Babul Ulum received new teaching materials in the form of Augmented Reality cards; The use of this learning media causes students to understand better and not get bored easily when the learning process takes place.